ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI STRUKTUR MODAL PADA PERUSAHAAN INDEKS LQ45 DI BEI PERIODE 2018-2022 - Astika, Binar; Astuti, Diana Dwi; Haifa, Haifa (RISTANSI: Riset Akuntansi, 2024)
The purpose of this study is to analyze the influence of asset structure, company size, profitability, business risk, and liquidity on capital structure, using companies listed in the LQ45 index on the Indonesia Stock Exchange (IDX) as the research objects. This research was conducted over five consecutive years, from 2018 to 2022, involving 16 companies selected through purposive sampling. The analysis method used is multiple linear regression. The results of the study indicate that, partially, asset structure, business risk, and liquidity significantly influence capital structure, while company size and profitability do not have a significant effect on capital structure. Simultaneously, asset structure, company size, profitability, business risk, and liquidity significantly influence capital structure.